2019
DOI: 10.1111/jpn.13144
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of vitamin C on biochemical and oxidative changes induced by acute exposure to diazinon in rat various tissues: Prophylactic and therapeutic roles

Abstract: Diazinon (DZN) as an organophosphate pesticide may cause oxidative stress in different tissues. Antioxidants increase tissue protection from oxidative stress. The aim of the present study was to investigate prophylactic and therapeutic effects of vitamin C against oxidative stress caused by DZN in various tissues of male Wistar rats. Thirty rats were divided into five groups: control group received corn oil as DZN solvent, DZN group received 100 mg/kg of DZN, C group received 200 mg/kg of vitamin C, C‐DZN and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Similarly, ROS produced from the metabolism of DZN may damage other tissues such as heart, kidney and spleen causing the leakage of enzymes from the tissues into plasma [21]. However, the reduced these parameters levels in groups pre-and post-treated with vitamin E showed that the antioxidant vitamin E protected the tissues from the lipoperoxidative changes provoked by DZN, probably due to its free radical scavenging ability [2,25]. Damodar et al [26] have reported that co-administration of vitamin E with DZN to rats resulted in insignificant improvement of the liver enzyme activities.…”
Section: Effects Of Treatments On Plasma Biochemical Parametersmentioning
confidence: 97%
See 3 more Smart Citations
“…Similarly, ROS produced from the metabolism of DZN may damage other tissues such as heart, kidney and spleen causing the leakage of enzymes from the tissues into plasma [21]. However, the reduced these parameters levels in groups pre-and post-treated with vitamin E showed that the antioxidant vitamin E protected the tissues from the lipoperoxidative changes provoked by DZN, probably due to its free radical scavenging ability [2,25]. Damodar et al [26] have reported that co-administration of vitamin E with DZN to rats resulted in insignificant improvement of the liver enzyme activities.…”
Section: Effects Of Treatments On Plasma Biochemical Parametersmentioning
confidence: 97%
“…The elevated these enzymes activities in DZN exposed rat may be due to leakage from the liver and heart tissues as a result of DZN-induced lipid peroxidation of membrane [24]. In addition, significant increases of plasma creatinine, urea and uric acid levels may due to the impairment of the glomerular function and tubular damage in the kidneys caused by DZN through induction of oxidative stress [2,5]. Similarly, ROS produced from the metabolism of DZN may damage other tissues such as heart, kidney and spleen causing the leakage of enzymes from the tissues into plasma [21].…”
Section: Effects Of Treatments On Plasma Biochemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 ] Although some studies have reported that SB‐treated rats showed anxiogenic behaviors and alteration in rats' cerebellar structure, [ 18,34 ] AA has been reported to have neuroprotective effects against neurotoxicity in rats. [ 33,35 ] There is contrasting information on the effect of Coadministration of SB and AA in vivo. Kehinde et al showed that AA coadministered with SB aggravated damage to male Wistar rats' testicular function.…”
Section: Introductionmentioning
confidence: 99%